The cortico-striatal circuitry in autism-spectrum disorders: a balancing act - Soghomonian, Jean-Jacques (Frontiers in Cellular Neuroscience, 2024)
The basal ganglia are major targets of cortical inputs and, in turn, modulate cortical function via their projections to the motor and prefrontal cortices. The role of the basal ganglia in motor control and reward is well documented and there is also extensive evidence that they play a key role in social and repetitive behaviors. The basal ganglia influence the activity of the cerebral cortex via two major projections from the striatum to the output nuclei, the globus pallidus internus and the substantia nigra, pars reticulata. This modulation involves a direct projection known as the direct pathway and an indirect projection via the globus pallidus externus and the subthalamic nucleus, known as the indirect pathway. This review discusses the respective contribution of the direct and indirect pathways to social and repetitive behaviors in neurotypical conditions and in autism spectrum disorders.